2015
DOI: 10.1186/s12968-015-0183-4
|View full text |Cite
|
Sign up to set email alerts
|

Vascular and plaque imaging with ultrasmall superparamagnetic particles of iron oxide

Abstract: Cardiovascular Magnetic Resonance (CMR) has become a primary tool for non-invasive assessment of cardiovascular anatomy, pathology and function. Existing contrast agents have been utilised for the identification of infarction, fibrosis, perfusion deficits and for angiography. Novel ultrasmall superparamagnetic particles of iron oxide (USPIO) contrast agents that are taken up by inflammatory cells can detect cellular inflammation non-invasively using CMR, potentially aiding the diagnosis of inflammatory medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 69 publications
2
37
0
Order By: Relevance
“…TEM images showed that labeled ASCs incorporate USPIO by endocytic mechanisms, as already reported. 29 It has been demonstrated that nanoparticles internalized by endocytosis often accumulate inside multivesicular bodies, 30 which, in turn, may fuse with the plasma membrane thus releasing their cargo (exosomes). 31 It is likely that USPIO undergo the same secretion process of the endosomal system.…”
Section: Discussionmentioning
confidence: 99%
“…TEM images showed that labeled ASCs incorporate USPIO by endocytic mechanisms, as already reported. 29 It has been demonstrated that nanoparticles internalized by endocytosis often accumulate inside multivesicular bodies, 30 which, in turn, may fuse with the plasma membrane thus releasing their cargo (exosomes). 31 It is likely that USPIO undergo the same secretion process of the endosomal system.…”
Section: Discussionmentioning
confidence: 99%
“…Based on their size, they are subdivided into several types, better suited for different applications (for example intravascular versus tissue imaging)(2). Their tissue accumulation causes local magnetic field inhomogeneities that can be measured by MRI (2).…”
Section: Iron Oxide Nanoparticles Imaging Of Plaque Inflammationmentioning
confidence: 99%
“…Based on their size, they are subdivided into several types, better suited for different applications (for example intravascular versus tissue imaging)(2). Their tissue accumulation causes local magnetic field inhomogeneities that can be measured by MRI (2). Alternatively, iron oxides (such as the dextran coated cross-linked iron oxide nanoparticles, CLIO, used in this work)(3), can be labeled with radioisotopes and/or fluorophores and functionalized as multi-modality imaging agents detectable by positron emission tomography (PET) or near infra-red fluorescence (NIRF) imaging, alone or in combination(4).…”
Section: Iron Oxide Nanoparticles Imaging Of Plaque Inflammationmentioning
confidence: 99%
See 1 more Smart Citation
“…T2 and T2*-weighted imaging provide a sensitive method of assessing USPIO accumulation in tissues. In this concise and well-written review, the authors address the basic concepts, developments and applications of novel USPIOS contrast agents for CMR studies of vascular inflammation and atherosclerotic plaques imaging [142]. …”
Section: Vascular Diseasementioning
confidence: 99%